KEADILAN DALAM PERSPEKTIF FILSAFAT ILMU HUKUM - Dwisvimiar, Inge (Jurnal Dinamika Hukum, 2011)
The author in this paper tries to investigate and describe the perspective of Justice in Legal Studies. Fairness in Legal Studies Philosophy attention to all aspects of terminology relating to justice and legal philosophy of science. Justice is the ideals and purposes of the law that reach from the philosophy of science perspective of the law by providing that justice is realized through law. By reviewing the opinion of Plato and Aristotle as the foundations of justice, Thomas Aquinas, who called for justice as well as John Rawls proportional equality with justice fairness the the basic values  of justice are included in the study of philosophy of science philosophy of law will be answered by the legal science it self.The justice is not just there and read the text of legislation but also the legal justice in society. Both Article 16 paragraph (1) Law 4/2004 and Article 5 paragraph (1) Law 48/2009 states that justice shall be upheld in spite of no normative provisions and how thejudge alone buat also to explore and understand the values and sense of justice that exists in the community.Key words: justice, legal studies, philosophy of science of law